2021
DOI: 10.1016/j.jpainsymman.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving Experience and Other Factors Associated With Having End-Of-Life Discussions: A Cross-Sectional Study of a General Japanese Population

Abstract: Context. The factors associated with end-of-life discussion (EOLD) are not well elucidated; an understanding of these factors may help facilitate EOLD. Objectives. To investigate the associations between EOLD and experiences of the death of and/or care for a loved one and other factors. Methods. Data from a nationwide anonymous questionnaire survey of public attitudes toward end-of-life medical care, conducted in December 2017 in Japan, were used. Participants were randomly selected from the general population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Given the COVID-19 pandemic, it has been reported that only 40% of community-dwelling individuals [ 21 ] and 60% of older adults living with diseases [ 22 ] have discussed their decision-making on EOL in Japan. With the increased interest due to the pandemic, municipalities need to ensure awareness campaigns on ACP.…”
Section: Discussionmentioning
confidence: 99%
“…Given the COVID-19 pandemic, it has been reported that only 40% of community-dwelling individuals [ 21 ] and 60% of older adults living with diseases [ 22 ] have discussed their decision-making on EOL in Japan. With the increased interest due to the pandemic, municipalities need to ensure awareness campaigns on ACP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the willingness of holding and EOL discussion is known to vary. The likelihood is higher for people who have played a caregiving role of a dying loved one in the past, and lower for males, younger consumers and those who do not have a family doctor [ 60 ]. Uptake of documented care plans may be hindered by lack of availability of care plans directives, ‘out of date’ plans, suboptimal documentation (wishes not clear enough and/or subject to misinterpretation), instructions which are not relevant to the current clinical situation, or families opposing execution of the care plan [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%